Soil structure and glyphosate fate under no-till manangement in the pampa region. II. Glyphosate and AMPA persistence and spatial distribution in the long-term. A conceptual model - Morras, Héctor José María; Behrends Kraemer, Filipe; Sainz, Daiana Soledad; Fernández, Patricia; Chagas, Celio Ignacio (Elsevier, 2022)
Glyphosate and AMPA were measured in a no-tilled (NT) soil and in the runoff resulting from the rain simulation carried out after 270 days of the application of the herbicide. Glyphosate concentration was in low values in runoff water but was not detected in the soil. In contrast, AMPA was found only in soil samples (same LOD/LOQ for both molecules). These intriguing results, on the one hand have led us to develop a conceptual model explaining the dynamics of glyphosate in NT soils with strongly developed platy structures resulting from this soil management, and, on the other hand, to underline the requirement of certain methodological precautions when analyzing properties of such stratified surface horizons. In our model, glyphosate was mostly degraded into AMPA although a small part remained adsorbed and trapped in the plates in the upper soil layer. In the field test, platy aggregates were destroyed by the raindrop impacts, glyphosate was washed off and transported in solution or bound to eroded soil particles. Glyphosate was not detected in soil analysis mainly due to the reduced volume of the surface plates in the total sample and, to a lesser extent, some loss of surface soil material during samples preparation due to its high content of roots and plant debris. In contrast, AMPA leached preferentially and became trapped in the micropores of the dense layer. Therefore, its absence in the runoff and its relatively high proportion in the soil would be due to its accumulation and preservation in the lower portion of the A horizon. The long persistence of AMPA would be explained not only by its physical occlusion in small pores preventing microbial accessibility, but also by a low diffusivity of oxygen and water restricting biotic and abiotic degra dation processes. It is suggested that an integrative approach considering both the physical behaviour and the architecture of the soil at different scales in the laboratory and in the field, can contribute to understanding the fate of glyphosate and other agrochemicals in NT soils.